2014
DOI: 10.1128/jvi.01849-13
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Benefits the Replication of Newcastle Disease Virus in Chicken Cells and Tissues

Abstract: bNewcastle disease virus (NDV) is an important avian pathogen. We previously reported that NDV triggers autophagy in U251 glioma cells, resulting in enhanced virus replication. In this study, we investigated whether NDV triggers autophagy in chicken cells and tissues to enhance virus replication. We demonstrated that NDV infection induced steady-state autophagy in chickenderived DF-1 cells and in primary chicken embryo fibroblast (CEF) cells, evident through increased double-or single-membrane vesicles, the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
96
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 55 publications
8
96
0
Order By: Relevance
“…A similar result was observed in the U251 glioma and chicken cells infected with NDV Beaudette C strain [32, 33]. However, the precise mechanisms by which autophagy promote viral replication remains unclear.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A similar result was observed in the U251 glioma and chicken cells infected with NDV Beaudette C strain [32, 33]. However, the precise mechanisms by which autophagy promote viral replication remains unclear.…”
Section: Discussionsupporting
confidence: 78%
“…It has been shown recently that NDV strain Beaudette C triggers autophagy both in human U251 glioma cells and in chicken cells leading to enhanced virus replication [32, 33]. However, it remains unclear how autophagy promotes viral replication.…”
Section: Introductionmentioning
confidence: 99%
“…The intracellular loads of pVP2 were similar with and without rapamycin treatment, but the intracellular and extracellular virus titers increased significantly in the presence of rapamycin (data not shown). A previous study showed that rapamycin does not induce obvious autophagy in DF-1 cells as it does in mammalian cells (32). Cells were starved of amino acids, a condition also known to induce autophagy (40).…”
Section: Resultsmentioning
confidence: 97%
“…Avian reovirus nonstructural protein p17 induces autophagy, resulting in enhanced virus replication (31). Furthermore, autophagy is beneficial to the replication of Newcastle disease virus in both chicken cells and tissues (32). These data highlight the remarkable diversity in term of strategies by which viruses subvert the autophagy pathway and raise the possibility that autophagic degradation could itself promote virus production.…”
mentioning
confidence: 92%
“…They used the ptfLC3 plasmid to show that siRNA knockdown of GAPR-1, a newly identified inhibitor of autophagy, increased autophagosome formation by causing an increase in autophagic flux rather than a block in autophagosome maturation. Another group studied of the role of autophagy in Newcastle Disease Virus (NDV) infection (38). This study showed that NDV infection induces autophagic flux in two different kinds of chicken cells.…”
Section: Discussionmentioning
confidence: 99%